2013
DOI: 10.1161/strokeaha.111.000334
|View full text |Cite|
|
Sign up to set email alerts
|

Foot Drop Stimulation Versus Ankle Foot Orthosis After Stroke

Abstract: Using either an FDS or an AFO for 30 weeks yielded clinically and statistically significant improvements in gait speed and other functional outcomes. User satisfaction was higher in the FDS group. Although both groups did receive intervention, this large clinical trial provides evidence that FDS or AFO with initial physical therapy sessions can provide a significant and clinically meaningful benefit even years after stroke. Clinical Trial Registration Information- URL: http://www.clinicaltrials.gov. Unique Ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
193
1
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 189 publications
(212 citation statements)
references
References 61 publications
9
193
1
9
Order By: Relevance
“…32 In addition, when chronic stroke patients with foot drops were applied to FES for 30 weeks, the subjects were found to be clinically effective in functional evaluation according to their FMA-LE, TUG test, and 6MWT. 33 Above-mentioned studies have shown beneficial to effects from long-term FES application. In the present study, short-term FES application with augmented feedback training also showed a significant effect on clinical measures in the same way as previous ones.…”
Section: Discussionmentioning
confidence: 99%
“…32 In addition, when chronic stroke patients with foot drops were applied to FES for 30 weeks, the subjects were found to be clinically effective in functional evaluation according to their FMA-LE, TUG test, and 6MWT. 33 Above-mentioned studies have shown beneficial to effects from long-term FES application. In the present study, short-term FES application with augmented feedback training also showed a significant effect on clinical measures in the same way as previous ones.…”
Section: Discussionmentioning
confidence: 99%
“…This study was a cross-sectional analysis of data that was obtained from 2 stroke rehabilitation trials, the LEAPS (Locomotor Experience Applied Post-Stroke) 12 and FASTEST (Functional Ambulation: Standard Treatment vs Electrical Stimulation) 11 trials. Inclusion criteria for both studies were diagnosis of stroke, able to walk ≥10 m with at most maximal assistance, and gait speed <0.80 m/s at start of the intervention.…”
Section: Methodsmentioning
confidence: 99%
“…More detail on the purpose, inclusion/exclusion criteria, and methods of these trials has been previously published. 11,12 This study does not report on the outcomes of either trial. Neither trial found a significant difference between groups for the primary or secondary outcomes.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations